Brand value co-creation as the structure of power - Limba, Tadas; Šidlauskas, Aurimas; Romeika, Giedrius; Juozėnaitė, Eglė (Transformations In Business & Economics, 2026)
Brand value co-creation is one of the most influential concepts in modern marketing. The involvement of consumers in a range of active activities, including development, feedback, advocacy, and support, can co-create brand value. Brands engage consumers in brand value co-creation by satisfying their needs. The benefits of brand value co-creation for companies include increased sales, market share, brand awareness, brand satisfaction, and consumer loyalty. The present article analyses brand value co-creation through Pierre Bourdieu“s approach to the structures of power. The investigative problem of this study is expressed through the following research question: What power structures do brands use in the brand value co-creation? The main objective of this paper is to analyse brand value co-creation through Pierre Bourdieu“s approach to the structures of power. The methods employed include scientific literature review, systematic and comparative analyses, semi-structured interviews, and generalization. The results of the study reveal that brand value co-creation functions as a power structure. This power manifests through the satisfaction of consumer desires and needs. In the case of the BMW brand, the brand allows consumers to express and create their identity, improve their image, belong to a community, and feel part of it. The BMW brand creates an attractive image that influences consumers“ thinking and behaviour in the direction desired by the brand, and consumers do not directly experience the effects of this power structure, as it exists in a way that is not directly understood. The study conducted 12 semi-structured interviews with members of the BMW brand community. It is revealed that most informants associated the brand with exclusivity, power, and high status. By internalising brand values and conforming to community norms, consumers may unconsciously recreate and reinforce brand power structures. This may involve symbolic violence, as the pressure to conform to brand-related standards may reinforce social inequality. Thus, brand value co-creation may function not only as a collaborative process but also as a mechanism that recreates power structures.